The Study of Learning Achievement in the Unit on Control Circuit Design Using Simulation Software, Employing Cooperative Learning with Competitive Group Techniques for Third-Year Vocational Certificate Students - จันทเสน อนวัช; วิชัย ขวัญภิรมณ์; บุญจินดา ดาวประกาย; ศักดิ์บุญญารัตน์ ธัญญพัทธ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this study were to 1) compare the learning outcomes of the control circuit design unit using simulation software before and after the implementation of cooperative learning with the competitive group technique among third-year vocational certificate students and 2) study the satisfaction of third-year vocational certificate students with cooperative learning using the competitive group technique. The sample consists of 25 students in the third year of the vocational certificate program, class MR. 3/1, at Eastern Technology College (E-Tech), selected through cluster sampling using the classroom as the sampling unit. The research instruments used include 1) a cooperative learning plan using the competitive group technique. 2) Achievement test and 3) Satisfaction questionnaire. The statistics used for data analysis include mean, standard deviation, and hypothesis testing using the Dependent t-test. The results revealed that 1) the comparison of learning outcomes in the unit on control circuit design using simulation programs showed that students who received cooperative learning with the competitive group technique had significantly higher post-test scores than pre-test scores at the .05 level, and 2) the evaluation of student satisfaction with the cooperative learning using the competitive group technique was overall at the highest level (Mean = 4.52, S.D. = 0.70).